The Moderating Role of Firm Size in the Relationship Between Board Size and Executive Incentives on Firm Performance - Khairani, Rizka; Lismawati, Lismawati (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study examines the effect of board size and executive incentives on firm performance in banking companies listed on the Indonesia Stock Exchange from 2020 to 2023. Firm size is tested as a moderating variable. A total of 45 banking companies were selected using purposive sampling, resulting in 180 firm-year observations, which were analyzed through panel data regression and Moderated Regression Analysis (MRA) using EViews 12. The results show that board size and executive incentives have a positive effect on firm performance, as measured by Return on Assets (ROA). However, firm size does not significantly affect firm performance and does not moderate the relationship between board size and performance. Notably, firm size negatively moderates the relationship between executive incentives and firm performance. These findings contribute to a better understanding of corporate governance dynamics in the banking sector.